The Use of Digital Health Services Among Patients and Citizens Living at Home: Scoping Review - Milla Rosenlund; Ulla-Mari Kinnunen; Kaija Saranto (JMIR Publications, 2023)
BackgroundThe development of digital health services reflects not only the technical development of services but also a change in attitude and the way of thinking. It has become a cornerstone for engaging and activating patients and citizens in health management while living at home. Digital health services are also aimed at enhancing the efficiency and quality of services, while simultaneously providing services more cost-effectively. In 2020, the COVID-19 pandemic accelerated worldwide the development and use of digital services in response to requirements for social distancing and other regulations. ObjectiveThe aim of this review is to identify and summarize how digital health services are being used among patients and citizens while living at home. MethodsThe Joanna Briggs Institute (JBI) methodology for scoping reviews was used as guidance. A search conducted in 3 databases (CINAHL, PubMed, Scopus) resulted in 419 papers. The reporting was conducted by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping review (PRISMA-ScR), and the analysis of the included papers was performed using a framework consisting of 5 clusters describing the use of digital health services. After screening and excluding papers that did not match the inclusion criteria, 88 (21%) papers from 2010 to 2022 were included in the final analysis. ResultsResults indicated that digital health services are used in different situations and among different kinds of populations. In most studies, digital health services were used in the form of video visits or consultations. The telephone was also used regularly for consultations. Other services, such as remote monitoring and transmitting of recorded information and the use the of internet or portals for searching information, were observed as well. Alerts, emergency systems, and reminders were observed to offer possibilities of use, for example, among older people. The digital health services also showed to have potential for use in patient education. ConclusionsThe development of digital services reflects a shift toward the provision of care regardless of time and place. It also reflects a shift toward emphasis on patient-centered care, meaning activating and engaging patients in their own care as they use digital services for various health-related purposes. Despite the development of digital services, many challenges (eg, adequate infrastructure) still prevail worldwide.